2021
DOI: 10.1038/s41598-021-89091-w
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-resolved genome assembly enables gene discovery in the red palm weevil Rhynchophorus ferrugineus

Abstract: The red palm weevil Rhynchophorus ferrugineus (Coleoptera: Curculionidae) is an economically-important invasive species that attacks multiple species of palm trees around the world. A better understanding of gene content and function in R. ferrugineus has the potential to inform pest control strategies and thereby mitigate economic and biodiversity losses caused by this species. Using 10x Genomics linked-read sequencing, we produced a haplotype-resolved diploid genome assembly for R. ferrugineus from a single … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…A high proportion of BUSCO core genes are expected to be present, complete, and single-copy in any genome, and deviations from this expectation are indicative of issues with assembly quality. In fact, Dias et al [ 70 ] have shown that this hybrid assembly [ 68 ] includes a high degree of artifactually duplicated sequences resulting from uncollapsed haplotypes, likely stemming from the use of a heterozygous sample containing multiple individuals. This implies that the unusually high rate of gene family expansion reported by Hazzouri et al [ 68 ] should be taken with caution and/or reassessed.…”
Section: Omics Technologies and Their Impact On Pest Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…A high proportion of BUSCO core genes are expected to be present, complete, and single-copy in any genome, and deviations from this expectation are indicative of issues with assembly quality. In fact, Dias et al [ 70 ] have shown that this hybrid assembly [ 68 ] includes a high degree of artifactually duplicated sequences resulting from uncollapsed haplotypes, likely stemming from the use of a heterozygous sample containing multiple individuals. This implies that the unusually high rate of gene family expansion reported by Hazzouri et al [ 68 ] should be taken with caution and/or reassessed.…”
Section: Omics Technologies and Their Impact On Pest Sciencementioning
confidence: 99%
“…In September 2021, a second draft genome was published for the RPW [ 70 ]. This assembly was produced from a single RPW larva using 10× Genomics linked reads.…”
Section: Omics Technologies and Their Impact On Pest Sciencementioning
confidence: 99%
“…Canu assembly of the S2R+ PacBio data displayed the highest level of BUSCO duplication (Figure 2B ) and the longest total assembly length ( Supplementary Table S1 ). We speculated that the high degree of BUSCO duplication in the Canu S2R+ assembly could be caused by haplotype-induced duplication artifacts in a partially-phased assembly that contained contigs from multiple haplotypes of the same locus ( 69 , 70 ). To test this, we took advantage of the fact that FALCON-Unzip leverages structural variants to phase heterozygous regions into a primary assembly (‘FALCON-Unzip_p’) and alternative haplotigs ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…To observe the synteny between the two beetle genomes, we combined the associations inferred from the MUMmer plot with the localization of the orthologous genes and constructed a Circos plot 39 (Circos, RRID:SCR_011798). Finally, 9,760 reciprocal best matches out of the total best hits (10,495) corresponded to orthologous genes between the 16 T. molitor scaffolds and the 10 T. castaneum chromosomes.…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…Previous efforts to produce T. molitor transcriptomes and more recently the draft genome using 10X genomics technology have been published 8 . While this latter technology was promising on diploid and heterozygous insects [9][10][11][12] , its application to T. molitor produced a fragmented assembly with a 90% of BUSCO completeness and no genome annotation. This particular effort motivated the development of a new genome assembly that would allow deeper genomic analyses such as quantitative trait locus mapping or genomic estimated breeding values analysis.…”
Section: Introductionmentioning
confidence: 99%